Genetic control of some plant architecture components in dry bean - Santos, João Bosco; Vencovsky, Roland (Pesquisa Agropecuaria Brasileira, 2014)
Eight bean (Phaseolus vulgaris L.) cultivars were crossed following a half-diallel model and data were obtained from the parents and F2generation in order to determine the genetic control of the insertion height of the first pod, length of the main stem, number and mean length of internodes at the main stem. A randomized block design with three replications was used in Lavras, MC, Brazil, in 1981. The method proposed by Hayman for analysing diallel crosses was used, and the data met the assumptions of the model. The additive gene action was predominant in relation to dominance for all traits. Consequently, one should consider means of the parents and of the F2 for each trait to carry out a breeding program. An additional technique for choosing the best segregant population, is to consider those with larger genetic variability. It is possible to obtain plants with ideal architecture components like high insertion of pods and many short internodes in main stem, from the F2 populations.